KEDUDUKAN DAKWAH DALAM PEMBANGUNAN BANGSA - Abd Rahim Arsyad (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2015)
Deterioration of morals in society is a problem that must be solved, Da'wah can mean to free mankind from the shirk, immoral and bad faith. It says the development bscause da’wah means the development of faith, monotheism, morality and welfare of life. Relation between da’wah and national development is purpose to growing up and Increasing faith and charitable objects of worship to preach so as to create a pious Muslim to Allah swt. and actively carry out development activities in the Republic of Indonesia based on Pancasila and the Constitution of 1945. Method used is descriptive to provide an understanding of full development.